Innovation using artificial intelligence in an advertising art classroom - Alsuwaida, Nouf; Alsamiri, Yasir (Frontiers in Education, 2025)
IntroductionThe current study investigated how students use artificial intelligence (AI) tools to enhance their learning in course activities, focusing on an advertising art course in a fine arts bachelor’s program at a Saudi Arabian university in Fall 2024.MethodsThis study used the Saudi Artificial Intelligence in Digital Learning (AIDL) framework and Technological Pedagogical Content Knowledge (TPACK) model to design AI activities in art classrooms. The research examined students’ perspectives on AI activities used in the course and the impact of using AI as a technological tool. A mixed-methods pilot design was used to produce an in-depth description of a small group with a specific duration and location. The sample of participants was purposely chosen: 30 female undergraduate students who registered for the course. Data were collected through the syllabus, observation, a survey, pre-and post-course tests, focus group discussions, and document and artifact analyses.ResultsSix themes emerged from the data. AIDL was revealed to be valuable and AI tools were deemed helpful in teaching and learning art and design concepts. The researcher integrated AI into their curriculum to help students understand the course requirements and improve their learning.DiscussionThe results indicate that these tools empower students to discover their unique talents and refine their skills in the arts and that teachers should incorporate TPACK and AIDL into curricula. Additionally, the findings imply that utilizing AI tools is essential for transforming teaching and learning methodologies in not only art and design but also other subjects. Finally, it benefits students’ understanding of course requirements and helps teachers effectively organize their courses.